Cellular interactions with hydrogel microfibers synthesized via interfacial tetrazine ligation. (October 2018) - Liu, Shuang; Moore, Axel C.; Zerdoum, Aidan B.; Zhang, Han; Scinto, Samuel L.; Zhang, He; Gong, Liang; Burris, David L.; Rajasekaran, Ayyappan K.; Fox, Joseph M.; Jia, Xinqiao
Abstract: Fibrous proteins found in the natural extracellular matrix (ECM) function as host substrates for migration and growth of endogenous cells during wound healing and tissue repair processes. Although various fibrous scaffolds have been developed to recapitulate the microstructures of the native ECM, facile synthesis of hydrogel microfibers that are mechanically robust and biologically active have been elusive. Described herein is the use of interfacial bioorthogonal polymerization to create hydrogel-based microfibrous scaffolds via tetrazine ligation. Combination of a trifunctional strained trans -cyclooctene monomer and a difunctional s -tetrazine monomer at the oil-water interface led to the formation of microfibers that were stable under cell culture conditions. The bioorthogonal nature of the synthesis allows for direct incorporation of tetrazine-conjugated peptides or proteins with site-selectively, genetically encoded tetrazines. The microfibers provide physical guidance and biochemical signals to promote the attachment, division and migration of fibroblasts. Mechanistic investigations revealed that fiber-guided cell migration was both F-actin and microtubule-dependent, confirming contact guidance by the microfibers. Prolonged culture of fibroblasts in the presence of an isolated microfiber resulted in the formation of a multilayered cell sheet wrapping around the fiber core. A fibrous mesh provided a 3D template to promote cell infiltration and tissue-like growth. Overall, the bioorthogonal approach led to the straightforward synthesis of crosslinked hydrogel microfibers that can potentially be used as instructive materials for tissue repair and regeneration.